Preparing Early Childhood Educators/Interventionists: Scoping Review Insights Into the Characteristics of Rural Practice. (March 2023) - Vilches, Silvia L.; Pighini, Maria J.; Stewart, Mary J.; Rossa-Roccor, Verena; McDaniel, Beth
Rural regions struggle to retain early intervention (EI), special education (SE), and early childhood education (ECE) supports for children with developmental delay and/or disability, yet there is little guidance to prepare pre-service students for rural practice. This exploratory scoping review of rural EI/SE/ECE practice in the United States and Canada, where EI for children birth to 8 years is part of the education and development continuum (as opposed to health), found four characteristics: a broader scope of practice, the importance of being a whole person, doing more outreach to engage families, and negotiating personal/professional boundaries. Retention is enhanced when educators feel effective and appreciated. Regionalized (not national) funding sources may be limiting disciplinary advances, and cultural/racial inclusivity, equity issues, travel, and distance barriers were under-studied. Cross-national variation in EI/SE/ECE terms impeded the search. Future research should highlight the unique multidisciplinary and multijurisdictional nature of rural EI/SE/ECE practice across the developmental span.